Climate risk management (CRM) and how it relates to achieving alignment with climate outcomes (ACO) - Caldecott, B (Taylor and Francis, 2020)
Instead of incidentally contributing to Alignment with Climate Outcomes (ACO) through Climate Risk Management (CRM) initiatives like the Task Force on Climate-related Financial Disclosures (TCFD), we need specific ways of dealing with and contributing to the challenge of alignment. These need to be articulated, developed, and scaled across the financial system rapidly. Without rebalancing the distribution of effort and spending more time explicitly on ACO, we cannot ever hope to align finance and the financial system with climate change objectives. One of the most significant things policymakers can do to spur rapid ACO is to make ACO targets and transition plans mandatory for all financial institutions as soon as possible.